Pola Asuh Orang Tua Dalam Membentuk Karakter Anak Berprestasi - Dwi Saputri, Mar'atul Latifah; Zainuri, Ahmad; Astrid, Annisa (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2020)
This research is motivated by the assumption that parenting is one of the factors that are very vital for the development of children and is part of the factors that can shape the character of children and make them achieve. The study explored parenting style employed by the parents in order to build the character of a successful child. The qualitative method was used in this study where the data were collected through interview, observation and documentation. The research participants were drawn by using purposive sampling technique. The participants were the parents of the children who frequently achieve the first till fifth rank in one of the elementary schools in east Lampung regency who tend to have many achievements. The data were analyzed using thematic analysis. From the result of data analysis, it was revealed that the parenting style to build the character of a achieving children is (1) Authoritative Parenting and (2) Authoritarian Parenting